Sins of the Night - Kenyon, Sherrilyn 1965- (New York St. Martin's Press, 2016)
"In the realm of the Dark-Hunters there is a code of honor that even immortal bad boys must follow: Harm no human. Drink no blood. Never fall in love. But every now and again a Dark-Hunter thinks himself above the Code. That's when I'm summoned. Who am I? I'm the one thing the fearless fear. Step over the line, and it's my wrath you will face. Nothing can touch me. Nothing can sway me. I am relentless and unfeeling. Or so I thought until I met a Dark-Hunter who goes by the name of Danger--it's not just her name, it's how she lives her life. She doesn't trust me at all. And who could blame her? I'm here to be judge, jury, and the executioner of her friends. Yet she is my key to saving some of them. Without her, they will all die. But as we try to save them, Dangereuse St. Richard is a deadly distraction. Something about her is reawakening feelings I'm not supposed to have. Especially compassion, which is a deadly emotion in a race against evil. The only hope mankind has is that I do my duty. And yet how can I do my duty when it means that I will have to sacrifice the only woman I've ever loved?"--
Keywords: Vampires -- Fiction; FICTION / Romance / Fantasy; FICTION / Fantasy / Contemporary; FICTION / Fantasy / Paranormal; FICTION / Fantasy / Urban Life; Paranormal romance fiction; Fantasy fiction; Love stories